2010
DOI: 10.1177/0003319710375087
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Femoral Intima-Media Thickness and the Severity of Coronary Artery Disease

Abstract: The carotid artery intima-media thickness (IMT) is an established surrogate marker of vascular risk. We assessed the common femoral artery IMT and its correlation with coronary artery disease (CAD). We also assessed the influence of vascular risk factors on the femoral IMT. Patients (n = 180; mean age 60.4 ± 10.5 years) who had undergone coronary angiography due to symptoms of CAD were enrolled in this study. We found significantly higher values of femoral IMT in patients with CAD than in those without CAD (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 29 publications
0
30
1
6
Order By: Relevance
“…[263032] In our study, we could not find any association for diabetes, hypertension, and smoking with carotid and aortic IMT. However, there were significant associations between age and dyslipidemia, and carotid and aortic IMT.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…[263032] In our study, we could not find any association for diabetes, hypertension, and smoking with carotid and aortic IMT. However, there were significant associations between age and dyslipidemia, and carotid and aortic IMT.…”
Section: Discussioncontrasting
confidence: 69%
“…Healthy age- and sex-matched control subjects[26] without evidence of cardiac diseases or symptoms were included. Control subjects had a normal treadmill test (TMT).…”
Section: Methodsmentioning
confidence: 99%
“…Our findings are consistent with previous studies. A number of studies demonstrated that there were significant correlations between femoral artery atherosclerosis and cardiovascular risk factors [25, 26]. A study by Kirhmajer et al reported that femoral intima-media was correlated with BMI ( r  = 0.16, p  = 0.036), high-density lipoprotein ( r  = − 0.30, p  = 0.0003), and triglycerides ( r  = 0.19, p  = 0.17) [26].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies demonstrated that there were significant correlations between femoral artery atherosclerosis and cardiovascular risk factors [25, 26]. A study by Kirhmajer et al reported that femoral intima-media was correlated with BMI ( r  = 0.16, p  = 0.036), high-density lipoprotein ( r  = − 0.30, p  = 0.0003), and triglycerides ( r  = 0.19, p  = 0.17) [26]. An AWHS study showed that the presence of subclinical femoral atherosclerotic plaque was associated with cardiovascular risk factors, such as dyslipidemia (OR, 1.46; 95% CI, 1.17–1.83), hypertension (OR, 1.66; 95% CI, 1.31–2.10), current smoking (OR, 3.88; 95% CI, 3.01–5.00), and diabetes (OR, 2.11; 95% CI, 1.20–3.70) [3].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Emerging evidence suggests that the femoral IMT has similar significant associations. 8,[12][13] Atherosclerotic scores incorporating data from angiograms of the common carotid and internal carotid arteries, carotid bifurcation, and femoral artery have been associated with far better assessments of the extent and severity of coronary artery disease than individual IMTs of either the carotid or femoral artery. [14][15][16] First Department of Cardiology, Athens Medical School Hippokration Hospital, Athens, Greece.…”
mentioning
confidence: 99%